Problemy zarządzania lasami na specjalnych obszarach ochrony siedlisk - Budniak, Piotr; Jabłoński, Marek; Kaliszewski, Adam (Leśne Prace Badawcze, 2025)
This paper discusses selected issues concerning the efficient management of forests overseen by the State Forest National Forest Holding, which are also protected as Natura 2000 sites. The study analysed the coherence of the provisions of the Forest Management Plans (PUL) and Natura 2000 Management Plans (PZO). The research was conducted in the first quarter of 2023 in six forest districts (Dukla, Jarocin, Kartuzy, Kołaczyce, Prudnik and Żednia) located within five regional directorates of the State Forests. The analyses carried out have identified several problems related to assigning the protection measures specified in the PZO to a specific area and determining their impact on forest management. The first problem concerns the boundaries of forest sub-compartments, which usually do not coincide with the boundaries of natural habitats (the protection measures apply to habitat areas rather than entire forest sub-compartments). Another fundamental problem is the discrepancy between the principles of forest management in the PUL and the the PZO regarding the area and location of natural habitats. A good example of this is the area PLH160007 – the Opawskie Mountains (Prudnik Forest District) and PLH200006 – Ostoja Knyszyńska (Żednia Forest District). The results of the phytosociological investigations in the Żednia Forest District revealed discrepancies in 55 sub-compartments where the 91D0 habitat was recorded according to the PZO. In 34 compartments, the phytosociological investigations showed that habitat 91D0 was not present. In the remaining 21 compartments, the investigations revealed either a different habitat area (with both positive and negative deviations) or a different natural habitat type. It also appears problematic to determine whether the changes in forest management envisaged in the PZO actually impose stricter restrictions on natural habitats than the economic model applied to areas managed by the State Forests outside Natura 2000 sites. It should also be emphasised that the provisions of the PZO regarding changes in forest management may overlap with, or even be less stringent than, those arising from other conditions and obligations, such as certification schemes (FSC and PEFC) and legal requirements for good practice in forest management. This creates a problem in assessing whether changes in forest management practices result solely from the establishment of the Natura 2000 site.